Application of Empowerment Pedagogy in Training of Future Primary School Teachers on the Basis of Sustainable Development - Chaikovska, Hanna (Educological discourse, 2023)
The problem of Empowerment Pedagogy has been studied in the psychological and pedagogical aspect and in the dimension of higher pedagogical education. Various approaches to the interpretation of the definition of the defined concept have been revealed. Emphasis is placed on the Pedagogy of Empowerment as a resource for self-discovery and self-education of future primary school teachers through activities in favour of sustainable development. The theoretical aspects of the given problem are studied on the basis of the analysis of the scientific literature, comparative and dialectical analysis of the obtained data. The potential possibilities of Empowerment Pedagogy in training of future primary school teachers to the professional activity considering the principles of sustainable development have been clarified. The impact of empowerment on the development of the strategy of individual independent activity of higher education seekers in the area of personal and professional responsibility has been revealed. The experimental study was conducted to verify the theoretical data involving students of the fourth year of study of the educational and professional program "Primary Education" of Ternopil Volodymyr Hnatiuk National Pedagogical University. Experimental training took place when teaching the elective course "Education for sustainable development in modern primary school" to future teachers. In the course of the research work, the impact of Empowerment Pedagogy on the ability of future primary school teachers to self-analyse and develop transformational empowerment activities was established. The results of control measurements showed an increase in the number of respondents with an active and transformational level of empowerment activities. Observations of the educational process testify to the increased awareness of future teachers of individual responsibility for sustainable development in the personal and professional spheres.